THE EFFECTIVENESS OF ROLE PLAY METHOD TOWARDS STUDENTS’ MOTIVATION IN SPEAKING SKILL - agustin wara prasetyanti (Language-Edu, 2020)
This study’ is aim to measure the effectiveness of the Role Play method on students’ speaking skill and on student’s motivation in learning speaking. This research was conducted in seventh grade students at SMP Negeri 5 Karangploso. The design of this research is quasi experimental research, consisted of two classes were experiment class and a control one. The research data were collected through a speaking test and questionnaire. The Shapiro-Wilk as a speaking test analyzed, while the questionnaire using a Likert Scale. Finding this research indicate that (1) the score in experiment class is higher than the score in control class,(2)the use of role play method can enhance the students’ five  components of speaking skill, (3) the learning process by using role play method fosters students’ interest, confidence and made fun in learning so as to improve speaking skill. In conclusion, using role play method had significant on students’ speaking skill towards students’ motivation.